Pesticide use and the case for toxicity-based taxation: evidence from citrus greening in Florida - Audrey Rizk; Ariel Singerman (Agricultural and Resource Economics Review)
Farmers make pest and disease management decisions without facing the social costs derived from their input choices. But given the sizable externalities involved, there is a rationale for government intervention. We model the profit-maximizing problem of a representative farmer by specifying a functional form for the damage function that incorporates the biological impact of the pathogen-vector system on yield as well as the abating impact of insecticides on the vector population. We use citrus greening disease in Florida as a case study because farmers there adopted an insecticide program that caused toxicity per acre to increase by 472%. Our simulation results show that a tax rate based on toxicity provides farmers with a strong incentive to substitute highly toxic chemicals with less toxic alternatives. Such a tax is also more efficient relative to a quantity-based tax that achieves a similar reduction in toxicity because it results in a significantly lower reduction in farmers’ yield and profit.